Period size effect induced crystalline quality improvement of AlN on a nano-patterned sapphire substrate. (2nd October 2019) - Xie, Nan; Xu, Fujun; Zhang, Na; Lang, Jing; Wang, Jiaming; Wang, Mingxing; Sun, Yuanhao; Liu, Baiyin; Ge, Weikun; Qin, Zhixin; Kang, Xiangning; Yang, Xuelin; et al.
Abstract: A comprehensive strategy of crystal quality control for AlN grown on a nano-patterned sapphire substrate has been explored based on the period size effect. It is found that the crystalline perfection of AlN can be greatly improved by enlarging the period size from 1.0 to 1.4  μ m, and the X-ray diffraction ω -scan FWHM values for (0002) and (10-12) planes reach 162 and 181 arcsec, respectively, owning to the significantly reduced area ratio of the coalescence zone. Our results indicate the pattern design requires a critical balance between reducing the area ratio of the coalescence zone and decreasing the coalescence thickness.